Influenza surveillance during 2015/2016 season in Portugal - Guiomar, Raquel (2017)
Background: The National Influenza Surveillance Program ensures influenza epidemiological surveillance, integrating clinical and laboratory data. The clinical component describes the transmissibility over time, the virological component detects and characterizes influenza virus in circulation. Data is generated through 2 sentinel surveillance structures, the General Practitioner’s Sentinel Network (since 1990) and the Network of Emergency Units (since 1999). Here we provide the evaluation of 2015/2016 influenza season in Portugal. Methods: Influenza-Like illness (ILI) cases were reported to the National Influenza Reference Laboratory and to the Epidemiology Department of the National Institute of Health, in the context of the National Influenza Surveillance Program, from week 39/2015 through week 20/2016. The intensity and duration of the epidemic period were described based on the weekly ILI incidence rates. Nasopharyngeal swabs were collected for influenza and other respiratory viruses (RV: respiratory syncytial virus, adenovirus, rhinovirus, metapneumovirus, coronavirus, parainfluenza virus) for diagnosis and characterization. The detection of influenza and RV was performed by multiplex real-time RT-PCR. Influenza virus isolation, antigenic analysis (hemagglutination inhibition assay) and genetic characterization (HA1 gene segment) were performed. Results: During 2015/2016 season the influenza activity was low and the epidemic period occurred between week 1/2016 and 9/2016 with a maximum of 59.4 ILI cases per 105 inhabitants in week 3/2016. No impact on mortality from all causes was observed in any age group. 1097 nasopharyngeal swabs were tested for influenza and other respiratory viruses, influenza was detected in 444 (41%) and others respiratory viruses were found in 265 (24%). The influenza A(H1)pdm09 was predominant (91% of flu confirmed cases). Influenza B/ Victoria was identified sporadically (7% of flu cases) in late season. A(H1)pdm09 were predominantly detected in adults aged 15-64. Other respiratory viruses were detected in influenza negative cases, being rhinovirus (101; 38%) and coronavirus (78; 29%) found in higher frequencies. The antigenic and genetic analysis of circulating influenza A(H1)pdm09 showed similarity with vaccine strain. The majority of influenza B virus belonged to Victoria lineage and clade 1A, dissimilar from 2015/16 vaccine strain. Although few A(H3) viruses in circulation, almost all were similar to strain recommended for next season, 2016/2017, influenza vaccine. None of the 420 A(H1)pdm09 viruses analysed showed the H275Y substitution, correlated to high reduced susceptibility to oseltamivir. Conclusions: Influenza activity during 2015/2016 flu season was low, that can be linked with a higher influenza activity in last season and exceptional climatic conditions during the winter (higher temperature than usual). A(H1pdm)09 viruses were dominant, although in co-circulation with influenza B/Victoria. Situation that contrasts with European influenza picture, that showed a late peak of influenza B/ Victoria. Influenza A(H1)pdm09 detections reached the highest percentage in adults (15-64 years old). Most influenza detected viruses were similar to the 2015/2016 vaccine strains, although circulating influenza B/Victoria were from a different lineage comparing with vaccine strain. Observed mortality from all causes was within expected values during study period.